Social and sustainability marketing : a casebook for reaching your socially responsible consumers through marketing science /: a casebook for reaching your socially responsible consumers through marketing science. (2021) - Bhattacharyya, Jishnu; Dash, Manoj Kumar; Hewege, Chandana; Makam, Sathyaprakash Balaji; Marc, Lim Weng
No abstract available